Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Can someone give an insight on the following problem? I'm not sure how to start the problem. It's a practice problem for "mean value theorem" and "Taylor's Theorem" so I'm assuming they might be necessary for the proof. Thanks!

Let $f: \mathbb{R} \to \mathbb{R}$ be a function. Suppose that $f$ is differentiable, that $f(0)=1$, and that $|f'(x)| \leq 1$ for all $x \in \mathbb{R}$. Prove that $|f(x)| \leq |x|+1$ for all $x \in \mathbb{R}$.

share|cite|improve this question
up vote 1 down vote accepted

Lets work by contradiction. Assume that $x\geq 0$ (I leave the negative reals for you) Suppose there is a point $x_0$ such that $f(x_0)>1+x_0$. (Note: Here $|x|=x$ since we are dealing with the non-negative reals) Then we have $$\frac{f(x_0)-f(0)}{x_0}>\frac{x_0+1-1}{x_0}=1,$$ so that by the mean value theorem there is a point $c\in (0,x_0)$ such that $f^'(c)>1$ which is a contradiction.

Hope that helps,

share|cite|improve this answer
thanks Eric it's really helpful! – Lindsay Duran Mar 8 '11 at 20:08

As an example, I will show how to prove something different using the mean value theorem.

$$|\cos y - \cos x| \leq |y - x|$$

The mean value theorem says that for $x \lt y$, there is some $c \in (x,y)$ such that

$f(y) - f(x) = (x-y) f'(c)$.

For instance, when when $f(x) = \cos x$ we have that

$\cos y - \cos x = (y-x) (-\sin c)$

Now if we take the modulus,

$|\cos y - \cos x| = |y - x| |\sin c| \leq |y - x|$, (as $|\sin c| \leq 1$).

Thus using the mean value theorem, we have proven that

$|\cos y - \cos x| \leq |y - x|$

Do you see how to solve your problem now?

share|cite|improve this answer

Try using the mean value theorem: for any $x$ we know there is some $a$ between $0$ and $x$ such that $$\frac{f(x)-1}{x} = f'(a)$$. Rearranging gives $f(x) = 1 + xf'(a)$. Now take absolute values and use the triangle inequality.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.